Fabrication of biodegradable PEG–PLA nanospheres for solubility, stabilization, and delivery of curcumin. (17th February 2017) - Liang, Hongying; Friedman, Joel M; Nacharaju, Parimala
Abstract: Curcumin is an effective and safe anticancer agent, and also known to induce vasodilation, but its hydrophobicity limits its clinical application. In this study, a simple emulsion method was developed to prepare biodegradable poly (ethylene glycol)–poly (lactic acid) (PEG–PLA) nanospheres to encapsulate curcumin to improve its solubility and stability. The nanoparticle size was around 150 nm with a narrow size distribution. Fluorescence microscopy showed that curcumin encapsulated PEG-PLA nanospheres were taken up rapidly by Hela and MDA-MB-231 cancer cells. This novel nanoparticulate carrier may improve the bioavailability of curcumin without affecting its anticancer properties.